Multicomponent compression system use in patients with chronic venous insufficiency: A real-life prospective study - Stücker, Markus; Münter, Karl Christian; Erfurt-Berge, Cornelia; Lützkendorf, Steffen; Eder, Stephan; Möller, Udo; Dissemond, Joachim (Journal of Wound Care, 2021)
Objective: Compression therapy is the cornerstone of therapeutic management of patients with chronic venous insufficiency (CVI). This study aimed to evaluate the efficacy and safety of a multicomponent compression system in an unselected population of patients with CVI problems under real-life conditions. Method: A prospective, multicentre, observational study with a multicomponent two-bandage compression system (UrgoK2, Laboratoires Urgo, France) was conducted in 103 centres in Germany. Main outcomes included wound healing rate, wound healing progression, assessment of oedema and ankle mobility, local tolerability and acceptance of the compression therapy. Results: A total of 702 patients with venous leg ulcers (VLU) and/or with lower limb oedema due to CVI were treated with the evaluated system for a mean (±standard deviation) duration of 27±17 days. By the last visit, 30.9% of wounds had healed and 61.8% had improved. Limb oedema was resolved in 66.7% of patients and an improvement of ankle mobility was reported in 44.2% of patients. The skin condition under the compression therapy was also considered as improved in 73.9% of patients and a substantial reduction of pain was achieved, both in number of patients reporting pain and in pain intensity. Compression therapy with the evaluated system was 'very well' or 'well' tolerated and 'very well' or 'well' accepted by >95% of patients. These positive outcomes were in line with the general opinion of physicians on the evaluated compression bandages, which were judged 'very useful' or 'useful' for >96.6% of patients. Similar results were reported regardless of the treated condition, VLU and/or limb oedema. Conclusion: Real-life data documented in this large observational study of non-selected patients receiving compression therapy in daily practice confirm the benefits and safety profile of the evaluated compression system. This study also confirms the high-level of performance and acceptability of the system, regardless of the characteristics of the wounds or patients at initiation of the treatment. The data support the use of this multicomponent compression system as one first-line intervention in patients with symptoms caused by CVI.
CRIS-Team Scopus Importer:2021-05-28
Keywords: Chronic venous insufficiency; Compression therapy; Leg ulcers; Lower limb oedema; Observational study; Oedema; Wound; Wound healing